Misconceptions of the Sabbath as Rest: The Social Interpretation of Exodus 23:1-12 and Its Relevance - Jusuf Haries Kelelufna; Sipora Blandina Warella; Brayen Aliong Patty; Dery Anthon Gaszpers; Yohanis Sefwin Noya (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2023)
This article is driven by the many problems related to Sunday activities and land problems in the Moluccas. According to J.H Elliott, the authors analyze the text of Exodus 23:1–12 using the social sciences critique method. Meanwhile, the theory used as an analytical tool is the Structural-Functional theory proposed by Emile Durkheim and Jean Jacques Rousseau’s social contract theory. The results of the analysis are then discussed in relation to the church context in the Moluccas. The study's results found that originally, Sabbath meant to rest within the context of work. "Work," as understood by the concept of Sabbath, means working with God in promoting social care, economic sustainability, and environmental concern. Misunderstandings of the Sabbath as Rest cause certain elements in the structure of Moluccan society not to function as they should because the Sabbath is misconstrued to perpetuate laziness, ignore others, hinder economic growth, and ignore the environment. In actuality, the Sabbath provides balance, not only balancing work with rest but also balancing rest with work. The Sabbath needs to be interpreted as 'working' in the context of communion with God, social care, guaranteeing economic sustainability, and concern for the environment. Local wisdom and regional culture as a social contract are still necessary in caring for humanity and preserving the territory, so such local wisdom and particular aspects of regional culture must be preserved and strengthened.